The Impact of Urbanisation and the Changing Environment of the Malay Settlement - Azli, Abdullah; Julaihi, Wahid; Ema Yunita, Titisari; Engku Nasri, Engku Mohd Ariffin (AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK, 2022)
It is acknowledged that “architecture is about people, culture, and land. However, the development of urban areas has raised many questions about the urban dream and the notion that it is “paved with gold.” The methodology of the study employs a mixed-method approach. According to the research, urban development is accelerating exponentially, and urban sprawl has occurred unpredictably, encroaching on traditional settlements. The new development on the outskirts of the old settlement is geared toward middle-income groups and is unattainable for the locals. Although the housing programme has been in place since 1968, it does not demonstrate the government’s total commitment and participation in assisting the Kelantanese urban population